Self-Management Education Programs for People Living with HIV/AIDS: A Systematic Review - Millard, T.; Elliott, J.; Girdler, Sonya (Mary Ann Liebert, Inc. Publishers, 2013)
The effectiveness of self-management programs to improve physical, psychosocial, health knowledge, and behavioral outcomes for adults living with HIV has not been well established. This article reviews the effectiveness of self-management education programs to improve physical, psychosocial, health knowledge, and behavior outcomes for adults living with HIV/AIDS. A systematic review of English articles using CINAHL, MEDLINE, and PsycINFO were used to identify and retrieve relevant studies. Each database was searched from its earliest record to October 2010. Search terms included HIV/AIDS, self-management, self-care, patient education, and education programs. Only studies that (1) reported on a HIV-specific intervention that aimed to increase participants HIV-related knowledge through a self-management component, (2) included a control group, (3) provided skills training or targeted behavior change, and (4) reported clinical outcomes were included. Independent data extraction by one author using the methods described in the Cochrane Handbook for Systematic Reviews. A second reviewer checked the data extraction. Six protocols were reported in eight publications (n=1178), all contained elements of self-management interventions. Effect size calculations were not conducted due to limitations in the available data. The review found randomized controlled trials (RCT) evidence sufficient to infer that self-management programs for people living with HIV/AIDS result in short-term improvements in physical, psychosocial, and health knowledge and behavioral outcomes. Statistically significant improvements were reported for intervention participants compared to control participants across most outcomes. There is insufficient evidence to provide conclusions regarding the long-term outcomes of HIV-specific self-management interventions.